(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the place of idea and ideology in the structure of social consciousness through philosophical, sociological and communicative approaches. The central thesis is that an idea functions as a meaning-generating, future-oriented and value-synthesizing element of social consciousness, whereas ideology transforms selected ideas into a stable semantic system, institutional practice, source of social legitimacy and mechanism of collective mobilization. The study reveals the functional role of idea and ideology within the interaction of everyday, theoretical, political, legal, moral, religious, aesthetic and scientific forms of social consciousness. Methodologically, the article relies on system-structural, historical-logical, hermeneutic, comparative and discourse-analytical methods. The findings show that idea and ideology are not peripheral ornaments of public thought; rather, they occupy a central position in processes through which society interprets itself, hierarchizes values, strengthens social solidarity, justifies modernization goals and develops moral immunity against information risks. At the same time, the article argues that ideology should not be reduced to propaganda or political rhetoric: it should be understood as a normative-communicative system that links production of meaning with ethical responsibility, legal culture and civic participation. The paper therefore proposes a stratified model of social consciousness in which idea represents the generative core of meaning and ideology represents the integrative architecture that connects meaning with institutions, identity and action.